2020
DOI: 10.1002/jssc.202000169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of matrix effect in one‐dimensional and comprehensive two‐dimensional liquid chromatography for the determination of the phenolic fraction in extra virgin olive oils

Abstract: Olea europaea, meaning “European olive,” is a small tree belonging to the family Oleaceae, occurring in the Mediterranean Basin. Olive oil is an essential component of a balanced diet because of its nutritional value. Among micronutrients, phenolic compounds did show important beneficial effects for human health. The majority of the research studies on the phenol content are carried out by liquid chromatography combined to photodiode array and/or mass spectrometry detection; however, because of matrix complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Furthermore, the values of LODs obtained ranged from 0.24 mg/L to 0.39 mg/L for apigenin and epicatechin, respectively; whereas, LOQs values were lower than 1.13 mg/L (Table 1). It has been demonstrated that LODs values in LC×LC are higher than 1D-LC, due to chromatographic dilution [28]. However, the LODs results attained in this work by LC×LC-PDA are comparable with the ones reported by a recent work at least for five compounds, namely catechin, epicatechin, quercetrin, quercetin, and kaempferol, analyzed by LC-UV [29].…”
Section: Development and Validation Of The Quantitative Methodssupporting
confidence: 73%
“…Furthermore, the values of LODs obtained ranged from 0.24 mg/L to 0.39 mg/L for apigenin and epicatechin, respectively; whereas, LOQs values were lower than 1.13 mg/L (Table 1). It has been demonstrated that LODs values in LC×LC are higher than 1D-LC, due to chromatographic dilution [28]. However, the LODs results attained in this work by LC×LC-PDA are comparable with the ones reported by a recent work at least for five compounds, namely catechin, epicatechin, quercetrin, quercetin, and kaempferol, analyzed by LC-UV [29].…”
Section: Development and Validation Of The Quantitative Methodssupporting
confidence: 73%
“…With regards to corrected peak capacity 2D n corr values, incorporating under-sampling [ 40 ] and A O values [ 38 ], the highest values were obtained for Samples 4 (1161) and 3 (1004), respectively. When comparing these values with previously reported ones, these were undoubtedly higher than RP-LC×RP-LC set-ups (695 in Wong et al [ 22 ], 461–633 in Arena et al [ 23 ], 404–639 in Arena et al [ 26 ]), despite slightly lower than similar HILIC×RP-LC set-up with active flow modulation (1605–1830 in Toro-Uribe et al [ 29 ]).…”
Section: Resultsmentioning
confidence: 49%
“…In this work the analysis of the polyphenolic compounds in R. coriaria samples was carried out by HILIC×RP-LC-PDA-ESI/MS. So far, most of the applications on polyphenols in food and natural products have been carried out on RP-LC×RP-LC [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], despite applications of HILIC×RP-LC also being reported [ 28 , 29 , 30 ]. Prior to either RP-LC×RP-LC or HILIC×RP-LC analysis, an optimization of the single separations must be carried out [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…LOD values are instead one or two orders of magnitude lower (Bartella et al, 2019(Bartella et al, , 2020 using multiple sector MS/MS instruments. Recent high-resolution equipment comes very close to these letter levels of sensitivity (Arena et al, 2020;Bajoub et al, 2020;Dini et al, 2020;Kanakis et al, 2013). In both approaches (MS/MS or HRMS), the increase in sensitivity is achieved by reducing the background noise due to interfering ions passing through the analyzer that are finally perceived by the detector.…”
Section: Ms Based Approaches For Bio-phenol Determination and The Com...mentioning
confidence: 99%